2021
DOI: 10.1016/j.jiph.2021.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 (IL-6) inhibitors as therapeutic agents for coronavirus disease 2019 (COVID-19): A systematic review and meta-analysis

Abstract: Introduction Preliminary study showed that coronavirus disease 2019 (COVID-19) disrupt body immune system including dysregulation of cytokine interleukin-6 (IL-6). IL-6 inhibitors agents have been used as treatment option for COVID-19, yet their benefit as therapeutic agent remain unclear. Objective We performed a systematic review and meta-analysis to synthesize the available evidence on the potential therapeutic effect of IL-6 inhibitor agents for the treatment of COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 37 publications
(103 reference statements)
1
24
0
8
Order By: Relevance
“…We found that the use of antibiotics, NSAIDs, steroids, convalescent plasma, IL6 inhibitors, and anticoagulants was associated with increased LOS but not with mortality. Other studies showed no difference in hospital LOS with steroid, convalescent plasma, or IL6 inhibitor use [33][34][35]. We attribute the association with increased LOS in our study to the need of staying in the hospital to complete the treatment course, which is supported by other studies [16,36].…”
Section: Discussionsupporting
confidence: 85%
“…We found that the use of antibiotics, NSAIDs, steroids, convalescent plasma, IL6 inhibitors, and anticoagulants was associated with increased LOS but not with mortality. Other studies showed no difference in hospital LOS with steroid, convalescent plasma, or IL6 inhibitor use [33][34][35]. We attribute the association with increased LOS in our study to the need of staying in the hospital to complete the treatment course, which is supported by other studies [16,36].…”
Section: Discussionsupporting
confidence: 85%
“…Future studies should accordingly investigate the IL-6 receptor blockade potential of tocilizumab therapy in the context of restricting the classical IL-6 signal in critically ill COVID-19 patients. This study did not nd credible evidence concerning the clinical correlation between thromboembolic events, IL-6 levels, and deaths among patients on tocilizumab therapy, The systematic review and metaanalysis by Pinzon et al (2021) revealed a strong relationship between IL-6 inhibitor drugs and mortality reduction in the setting of COVID-19 [39]. The ndings also revealed the potential of IL-6 inhibitors (including tocilizumab) to minimize the length of hospital stay and mechanical ventilation requirements among the COVID-19 patients on tocilizumab therapy.…”
Section: Discussionmentioning
confidence: 73%
“…Future studies should accordingly investigate the IL-6 receptor blockade potential of tocilizumab therapy in the context of restricting the classical IL-6 signal in critically ill COVID-19 patients. This study did not nd credible evidence concerning the clinical correlation between thromboembolic events, IL-6 levels, and deaths among patients on tocilizumab therapy, The systematic review and meta-analysis by Pinzon et al (2021) revealed a strong relationship between IL-6 inhibitor drugs and mortality reduction in the setting of COVID-19 [38]. The ndings also revealed the potential of IL-6 inhibitors (including tocilizumab) to minimize the length of hospital stay and mechanical ventilation requirements among the COVID-19 patients on tocilizumab therapy.…”
Section: Discussionmentioning
confidence: 74%